Evaluation of the Quezon City Public Library System's nonvisual desktop access service in assisting the blind and the visually impaired with the implication on its promotion and service delivery - Liwag, Marijoy G.
Since public libraries offer services to make their libraries accessible to people with disabilities particularly to the blind and the visually impaired, it is important that these services are evaluated to know if the library serves it purpose in assisting the blind/visually impaired and to further improve it. The Quezon City Public Library (QCPL) installed NonVisual Desktop Access (NVDA), a computer screen reader in 16 of their branches in 2011 but only 10 among those have maintained the NVDA service until today. The goal of this study was to evaluate the NVDA service of the QCPL for the blind and the visually impaired in order to come up with ideas on how can the QCPL improve the service.